THE CHILD AND THE INTERNET: SAFE LIVING TECHNOLOGIES - Volkova, Maria; Lavrentieva, Maria; Kuchenin, Evgeny; Lenkovskaya, Renata (Revista Inclusiones, 2020)
The authors have conducted a study of the main factors that ensure the information security of minors on the Internet, as well as have offered the classification of today’s threats to information security, and measures aimed at ensuring the information security of minors. The conducted analysis has allowed identifying measures of an organizational, legal, and technical nature, as well as considering the dissemination of best social practices. Considered threats concern the information content, communications, consumer, and electronic risks. A comparative analysis of foreign legislation has allowed providing a typology of countries based on the principle of differences in value indicators, and concluding that it is necessary to take into account national peculiarities in terms of two aspects: forming a national system of information security for minors and determining the category of information, dangerous for a child.